Reduction of death anxiety in patients with advanced cancer in short-term psychotherapy - Oberth, Paula; Springer, Franziska; Lehmann-Laue, Antje; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2025)
IntroductionThe fear of one’s own dying, death anxiety, has increasingly become the focus of research in recent years. So far, we know little about the reduction of death anxiety through psychotherapeutic interventions in patients with advanced cancer and possible predictors of this reduction. The aim of this study is to investigate the extent to which death anxiety is reduced during the course of psychotherapeutic interventions and whether specific socio-demographic, psychological or medical variables can predict such reduction over time.Materials and methodsThis study is a secondary data analysis of the randomized controlled trial on the effectiveness of Managing Cancer and Living Meaningfully (CALM) Therapy, a short-term psychotherapy used to reduce depression and psychological distress in patients with advanced cancer. The active control group, a non-specific psychotherapeutic counselling intervention (SPI), showed equal effects on depression and distress and consequently both groups are investigated together in this study. Within the present study, we analyze the reduction of death anxiety from baseline to 3- and 6-months follow-up. Data were collected using validated questionnaires; death anxiety was assessed using an adapted version of the Death and Dying Distress Scale (DADDS). Predictors of the reduction of death anxiety were investigated using multiple linear regression models.ResultsThe sample comprised 194 patients (average age 58 years, 62% female, all with a UICC stage of III or IV). There was a significant reduction of death anxiety over time, in particular between the baseline and 3 months follow-up [t (148) = 5.26, p < 0.001, d = 0.43] and between the baseline and 6 months follow-up [t (120) = 5.48, p < 0.001, d = 0.50]. The UICC disease stage III (p = 0.05) as well as an elevated death anxiety score/level at baseline (p = 0.01) were found to be predictors for the reduction of death anxiety. No further sociodemographic and medical predictors were found within the study.ConclusionThe study results suggest that psychotherapeutic interventions could reduce death anxiety in patients with advanced cancer. A time effect cannot be excluded and further studies using a care-as-usual control group are necessary. Nevertheless, this study sheds light on the role that psychotherapeutic interventions play in reducing death anxiety and complements the use of palliative medical treatments to alleviate patients’ discomfort.